FORECAST OF SUSTAINABLE ENERGY DEVELOPMENT IN SLOVENIA - Matevž Obrecht; Matjaž Denac (Journal of Energy Technology, 2024)
The development of the energy industry is strongly correlated with technology forecasting, which can provide core information for the planning of future energy policy. Energy policy must adhere to theglobal development paradigm in accordance with energy demand, population growth, global trends, environmental, and legislative restrictions, as well as the specific aspects of specific geographical areas. Reliable data on future trends are crucial for setting up an effective energy policy; therefore, results from a Delphi survey are essential for policy design. This paper presents the most significant findings gathered in the Delphi survey regarding future sustainable energy development in Slovenia. The results have revealed that achieving an increase in energy efficiency and a decrease in final energy consumption is much more important than maintaining low energy prices. The study has also forecast that the prices of all energy sources, including fossil fuels and wood biomass, will increase by 2020 and again by 2030. Delphi also forecast that Slovenia will transition to sustainable energy industry by 2046. The investments favoured by energy experts are small and micro hydro-electric power plants as well as cogeneration units.